Legal principles of international cooperation of the National Police of Ukraine with foreign law enforcement agencies - V. V. Pylyp (Bulletin of Kharkiv National University of Internal Affairs)
Rapid integration processes require the establishment of effective cooperation both between governments and between their individual bodies, institutions and organisations in all spheres of society. Law enforcement activity is no exception, since its effective implementation is a guarantee for ensuring the formation of a security space both on the territory of the state and on its borders.